Pedagogical content knowledge reconceived: Bringing curriculum thinking into the conversation on teachers' content knowledge - Deng, Zongyi (Teaching and teacher education, 2018)
This article contributes to a reconceptualization of pedagogical content knowledge through exploring what is entailed in teachers' understanding of content within the framework of the institutional curriculum, with a central concern for the development of human powers (capacities or abilities, ways of thinking, understanding worlds). The contribution is made by way of a curriculum making framework and through examining the capabilities approach and Bildung-centered Didaktik. The central thesis is that a teacher necessarily interprets the content contained in the institutional curriculum, identifying its elementary elements and ascertaining its educational potential. The interpretation calls for curriculum thinking informed by a theory of content. •PCK is reconceived to account for teachers enacting the institutional curriculum.•Teachers' interpretation of content entails curriculum thinking.•Selecting pedagogical forms entails ascertaining content educational potential.•A theory of content stands for teachers' curriculum knowledge.